Purchasing celebrity-endorsed brands as a way of self-presentation - Yue, Xiaofan; Abdullah, Nawal Hanim; Ali, Mass Hareeza; Raja Yusof, Raja Nerina (Inderscience Publishers, 2024)
The effectiveness of celebrity endorsement is a much-discussed topic in marketing, and this article aims to relate the celebrity's status, reputation and congruence with the consumer's ideal self to the brand's status, reputation and congruence to the consumers' ideal self. Thus, because of these brands' attributes and relation to the consumer's ideal self, consumers who need to use brands for self-presentation may have higher purchase intentions (PIs) and celebrity-endorsed brands. We used 245 survey samples to prove that a celebrity's status, reputation and congruence with the consumer's ideal self can be transferred to the endorsed brands, and the brand's status, reputation, and ideal self-congruity are positively related to the consumer's PIs. The consumer's need for self-presentation mediates the relationship between the brand's status and PIs and the relationship between brand ideal self-congruity and PIs.